The Position of the Financial Audit Agency in Examining Regional Financial Management and Responsibility of West Sumatra Province - Henny Andriani; Daswirman (Master of Law Program, Ekasakti University, 2024)
State finances are the backbone of a nation's development and play an important role in its economic sustainability. The Financial Audit Agency (BPK), as an independent and autonomous audit institution, is responsible for overseeing financial management and accountability, including at the provincial level, such as in West Sumatra. However, practical challenges hinder its effectiveness. In 2021, the West Sumatra BPK identified twelve problems in the West Sumatra Provincial Government's financial report, involving an outstanding amount of Rp. 12,058,560,000 which has not been handled by officials. Although Article 20 of Law no. 15 of 2004 mandates officials to follow up on audit findings within 60 days. This failure has damaged public trust in the BPK. This research aims to evaluate the role of the BPK in auditing financial management in West Sumatra Province and to explore the implications of unaddressed audit findings for democracy in Indonesia. Through a normative juridical approach, this research analyzes regulatory law and relevant public perceptions of the BPK. The findings show that although the BPK plays an important role, difficulties in enforcing its audit recommendations weaken its authority and affect public trust in democratic governance.